2013
DOI: 10.1159/000351168
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Anemia in Relation to Thalassemia and Iron Deficiency among Vietnamese Pregnant Women

Abstract: Background and Aims: Information about the extent to which anemia is related to thalassemia and iron deficiency (ID) is not available in Vietnam. This study investigated the burden of anemia in relation to thalassemia and ID among Vietnamese pregnant women. Methods: A cross-sectional study was conducted in Thua Thien Hue, Central Vietnam. Blood samples taken from 399 pregnant women with a gestational age <12 weeks were analyzed. Anemia was defined as Hb levels <11 g/dl, and ID as ferritin values <15 ng/ml. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…<11 gm/dl), while 14 women had SFC<15 ng/ml, for a frequency of anemia, ID and IDA of 19.3%, 15.9% and 11.4%. These figures coincided with that previously reported by Sukrat et al (2) and Siridamrongvattana et al (3) and with the recently reported by Nguyen et al (25) who found 20% of pregnant women were anemic, 14% had low iron stores and 3% had IDA and by Okafor et al (26) who detected ID and IDA in 20% and 17.9% of pregnant women.…”
Section: Discussion:-supporting
confidence: 92%
See 1 more Smart Citation
“…<11 gm/dl), while 14 women had SFC<15 ng/ml, for a frequency of anemia, ID and IDA of 19.3%, 15.9% and 11.4%. These figures coincided with that previously reported by Sukrat et al (2) and Siridamrongvattana et al (3) and with the recently reported by Nguyen et al (25) who found 20% of pregnant women were anemic, 14% had low iron stores and 3% had IDA and by Okafor et al (26) who detected ID and IDA in 20% and 17.9% of pregnant women.…”
Section: Discussion:-supporting
confidence: 92%
“…<11 g/dl) the highest prevalence of anemia and IDA during pregnancy was 14.1% and 6%, respectively. Thereafter, Siridamrongvattana et al (3) reported ID and IDA prevalence of 20.1% and 6%, respectively, of their series of pregnant women. On contrary, Breymann (1) documented that worldwide prevalence of ADI ranged between 20%-80% and consists of a primarily female population.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 98%
“…In this issue of Acta Haematologica , Siridamrongvattana et al [4] report in a cross-sectional study of 399 women in the first trimester of pregnancy in central Vietnam that they found an unexpectedly low prevalence of anaemia (19.3%), iron deficiency (20.1%) and iron-deficiency anaemia (6%). Interestingly, the authors also found that most of the burden of anaemia could not be explained by iron deficiency: 31% of anaemic women had iron deficiency (ferritin <15 μg/l), 26% were found to have a thalassaemia mutation, and the remaining 43% of anaemic women had apparently replete iron stores and no evidence of haemoglobinopathy.…”
mentioning
confidence: 99%
“…The continued practice of attributing 50% of cases of anaemia to iron deficiency, and of using anaemia to indicate the prevalence of iron deficiency, may need to be reviewed. As performed by Siridamrongvattana et al [4], a concerted effort to map and distinguish the epidemiology of anaemia from the epidemiology of haemoglobinopathy, malaria and iron deficiency in different low-income settings is needed.…”
mentioning
confidence: 99%
“…Iron deficiency is a major cause of anemia but other factors including infection, inflammation, and other nutrient deficiencies have been recognized as important contributors to its etiology as well [5] , [7] , [8] . In a previous analysis from our group, we reported that nearly 20% of the non-pregnant WRA in this Vietnamese population were anemic, but iron deficiency anemia was relatively low, occurring in only 1.9% of women [9] .…”
Section: Introductionmentioning
confidence: 99%